Modernising vocational education and training : fourth report on vocational training research in Europe: background report. Volume 1 - Descy, Pascaline [Mitarbeiter]; Tchibozo, Guy [Mitarbeiter]; Tessaring, Manfred [Mitarbeiter]; Ward, Terry [Mitarbeiter]; Tsakarissianos, Giorgos [Mitarbeiter]; Preston, John [Mitarbeiter]; Green, Andy [Mitarbeiter]; Strietska-Ilina, Olga [Mitarbeiter]; Smits, Wendy [Mitarbeiter]; Borghans, Lex [Mitarbeiter]; Golsteyn, Bart [Mitarbeiter] (Office for Official Publications of the European Communities, 2008)
"The series of reports on vocational education and training (VET) research have been published by Cedefop since 1998. The reports give a comprehensive review of current socioeconomic research related and relevant to VET and skill development in Europe, its results and implications for policy and future research. Research reports are a tool for evidence-based policy making. Attention is always paid to the theoretical and methodological foundations of research. Each research report consists of a background report of several volumes with contributions from renowned researchers of which this is one and a synthesis report written by Cedefop experts. Fourth research report: modernising vocational education and training Modernising VET is the overarching theme of the fourth research report. It aims to provide and discuss the evidence-base for the process of enhanced cooperation in VET which sets priorities for reforming VET to contribute to the Lisbon process. This fourth research report aims to document, discuss and analyse the socioeconomic context, and process of reforming VET, based on latest research evidence. The report intends to inform and improve policy-making and develop the VET research agenda." (Hrsg.)
Keywords: L 6.2.3 Evaluation; S 2.3 Berufsbildungspolitik; T 1.5 International vergleichende Berufsbildungsforschung; Berufsbildung; Modernisierung; Mobilität; Bildungsertrag; Berufsbildungsforschung; Berufsbildungspolitik; Europa